Islamic banking patronizing behavior in Mauritius: does religion matter? - Ramjaun, Shaheen; Abduh, Muhamad (2014)
Islamic banking in Mauritius is a very new industry introduced only in late 2007. Mauritius is a secular country with mostly people from Hinduism faith and only around twenty percent are Muslims. In such an environment, Islamic bankers would need to know whether the Mauritian population is willing to accept this new form of banking. This study attempts to investigate the willingness of the people of Mauritius to patronize Islamic banking and whether religion plays a significant role upon this issue. A survey was conducted and a logistic regression was carried out. The results show that mostly Muslims are more willing to choose Islamic banking as an alternative. Interestingly, descriptive statistics show that majority of respondents believed that Islamic banking is meant for everyone and not only for people of Islamic faith.